2015
DOI: 10.1007/s12011-015-0325-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Copper and Zinc in Patients with Rheumatoid Arthritis: a Meta-analysis

Abstract: Many publications with conflicting results have evaluated serum levels of copper (Cu) and zinc (Zn) in patients with rheumatoid arthritis (RA). To derive a more precise estimation of the relationship, a meta-analysis was conducted. Relevant published data were retrieved through PubMed, Chinese National Knowledge Infrastructure (CNKI), and Chinese Biomedical Database (CBM) before September 20, 2014. Weighted mean difference (WMD) with a 95 % confidence interval (95 % CI) was calculated using STATA 11.0. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 46 publications
7
32
0
1
Order By: Relevance
“…Although none of these mechanisms were explicitly examined in our study, PICRUSt analysis demonstrated that, compared with controls, the patient's microbiota facilitates copper transport and inhibits zinc transport. This finding may explain the higher copper levels and the lower zinc levels found in RA patients than in healthy subjects [45]. These trace elements are essential to many human biological processes, since they play a role in the functionality of enzymes and post-translational regulatory protein [46], with significant effects on cell regulation in both the adaptive and the innate immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Although none of these mechanisms were explicitly examined in our study, PICRUSt analysis demonstrated that, compared with controls, the patient's microbiota facilitates copper transport and inhibits zinc transport. This finding may explain the higher copper levels and the lower zinc levels found in RA patients than in healthy subjects [45]. These trace elements are essential to many human biological processes, since they play a role in the functionality of enzymes and post-translational regulatory protein [46], with significant effects on cell regulation in both the adaptive and the innate immune systems.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Many biological factors have been indicated to act as potent post-transcriptional repressors of collagen synthesis in skin fibroblasts and have been shown to be potential therapeutic targets for scar reduction. 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…Its significance as a structural component in proteins [ 2 ] and its participation in numerous cellular functions include, but are not limited to, cell proliferation and differentiation [ 3 , 4 ], RNA and DNA synthesis [ 5 , 6 ], stabilization of cell structures/membrane [ 7 , 8 ], as well as redox regulation [ 9 , 10 ], and apoptosis [ 11 , 12 ]. Zinc is involved in various metabolic and chronic diseases such as: type 1 diabetes, rheumatoid arthritis, cancer, neurodegenerative diseases, and depression [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Moreover, there is also strong evidence between zinc deficiency and several infectious diseases such as shigellosis, acute cutaneous leishmaniosis, malaria, human immunodeficiency virus (HIV), tuberculosis, measles, and pneumonia [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%